PTH-172 Outcome Assessment of the First Two Years of a New Oesophageal High Resolution Manometry Unit within a District General Hospital. (4th June 2013) - Bhangu, N K; Shieh, S C; Cacciattolo, T; Millman, S; Geary, R; Johnson, M W
Abstract : Introduction: Oesophageal high resolution manometry (OHRM) is a fast developing area of medicine. Whilst seemingly being at the "cutting edge" of technological advancement, it is a relatively simple procedure to perform and interpret. Its ability to demonstrate functional as well as anatomical abnormalities, has led to a range of new diagnoses and shed light on areas of previous clinical and management dilemma. Despite this, few hospitals outside of the large central teaching hospitals, have embraced this new technology. Objective: To assess the demand for OHRM within a district general hospital (DGH). To assess the reasons for referral and the general outcomes from the procedure. Methods: The Luton & Dunstable Hospital set up a new OHRM service in July 2009. Prospective procedure related information was stored on a HRM database. This database was analysed to assess total number of procedures performed, the reasons for referral and the diagnostic outcome of those procedures. Results: Over the course of the first 2 years, a total of 162 procedures were performed. Patients were referred in with a range of symptoms, often in combinations. Of these 162 patient 9 suffered dental problems, 31 had globus, 32 had persistent sore throat, 27 had chronic cough, 13 had nocturnal cough, 118 had endoscopic negative reflux-like symptoms, 40 had endoscopy negative dysphagia, 30 had atypical chest pains, 1 had persistent nausea, 24 had dysphonia and 2 were for reflux assessment. A wide range of diagnoses were made often in combination, including; - 52 with reduced LOS pressures, 18 with a small LOS, 58 with a hiatus hernia, 52 with acid reflux, 40 with non-acid reflux, 75 with oesophageal dysmotility, 23 with oesophageal spasm, 6 with hypertonic contractions, 19 with hypotonic dysmotility, 5 with achalasia type 2, 4 with achalasia type 3, 15 with a wide transition zone, 17 with transient LOS relaxation, 3 with poor pharyngeal co-ordination, 1 with food bolus, and 20 who were normal. Conclusion: OHRM is relatively simple procedure to perform and interpret. With its ability to diagnose both functional and anatomic abnormalities it has become an invaluable part of our DGH gastroenterology unit. Given the clear benefits over standard manometry, we believe that all patients throughout UK should have access to an OHRM service. Disclosure of Interest: None Declared.